2021
DOI: 10.1002/nafm.10712
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Spatial Structure of Invasive Lake Trout in Yellowstone Lake to Improve Suppression Efficacy

Abstract: Invasive Lake Trout Salvelinus namaycush have altered the once-pristine Yellowstone Lake ecosystem through top-down effects by consuming Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri. To conserve Yellowstone Cutthroat Trout and restore the ecosystem, a Lake Trout gillnetting program was implemented to suppress the invasive population. We evaluated the spatial structure of Lake Trout in Yellowstone Lake with the intent of increasing suppression efficiency. Specifically, we addressed questions relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 78 publications
(101 reference statements)
3
33
1
Order By: Relevance
“…Telemetry studies have shown that lake trout exhibit extensive seasonal movements and spawn in distinct locations within Yellowstone Lake (Williams 2019;Gutowsky et al 2020); however, we were unable to detect specific natal origins or movement patterns within the lake using otolith microchemistry. Though our negative results were not wholly unexpected, previous studies have shown microchemistry can detect natal origin differences in freshwater and marine fish separated by as little as 5-11 km geographic distance (Kennedy et al 2000;Chittaro & Hogan 2013).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Telemetry studies have shown that lake trout exhibit extensive seasonal movements and spawn in distinct locations within Yellowstone Lake (Williams 2019;Gutowsky et al 2020); however, we were unable to detect specific natal origins or movement patterns within the lake using otolith microchemistry. Though our negative results were not wholly unexpected, previous studies have shown microchemistry can detect natal origin differences in freshwater and marine fish separated by as little as 5-11 km geographic distance (Kennedy et al 2000;Chittaro & Hogan 2013).…”
Section: Discussioncontrasting
confidence: 62%
“…Novel techniques 4 to increase mortality of lake trout embryos on spawning sites are also being developed (Thomas et al 2019;Koel et al 2020b). A total of 14 spawning sites have been located and verified by the presence of gametes (Figure 1; Koel et al 2020b) with additional sites identified as probable spawning areas (Williams 2019). An understanding of the relative importance of spawning sites in producing pre-recruit lake trout could help direct gillnetting operations and embryo suppression efforts to the most productive sites and increase efficiency of the suppression program.…”
Section: Introductionmentioning
confidence: 99%
“…2021; Williams et al. 2022). Lake Trout in our study also aggregated at all spawning sites that were previously identified by Cox (2010) as hosting spawning activity, confirmed in spawning substrate located along Swan Lake's eastern shore, thus re‐affirming the locations as preferred spawning sites.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and stage of maturity were determined by visual observation of the gonads through the surgical incision (Williams et al. 2022). Lake Trout selected for transmitter implantation had testes or ovaries that were easily identifiable as mature; immature Lake Trout were not tagged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation